Komunikasi Manajemen dalam Peningkatan Nilai Sakip Direktorat Jenderal Pendidikan Anak Usia Dini Pendidikan Dasar dan Menengah Kementerian Pendidikan Kebudayaan Riset dan Teknologi - Tora Akadira (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
The Government Agency Performance Accountability System (SAKIP) is an integration of the planning, budgeting, and performance reporting system that is in line with the implementation of the financial accountability system of each government institution. The Directorate General of Early Childhood Education seeks to increase the value of SAKIP from year to year. Implementing the role of the organization and the environment will lead to interactions that give rise to norms, ethics and rules in society. The institutional theory holds that organizations will survive and adapt to changes in the existing environment, both economically and socially. Even between the organizational environment and other organizational environments, there will be an exchange of values, norms, rules and beliefs through acculturation and assimilation. Factors that can affect the success or failure of implementing a performance measurement system are divided into two categories: technical factors, including difficulty determining performance measures and limitations of information systems, and organizational factors, including management commitment, decision-making authority, and training. In this study, we will look at management commitment as a factor in increasing the value of SAKIP. Based on the results, it turns out that the management committee of the Directorate General of Early Childhood Education is an essential factor in achieving the Directorate General of Early Childhood Education's SAKIP. Management commitment will oversee starting from planning to evaluating the implementation of the Directorate General of Early Childhood Education SAKIP.